Enwildering the Lab: Merging Field Evaluation with In-Lab Experience Sampling - Niforatos, Evangelos; Karapanos, Evangelos; Alves, Rui; Martins, Maria Clara Correia; Chen, Monchu; Nunes, Nuno (My University, 2013)
While the Experience Sampling Method is considered the gold standard of in-situ measurement, researchers have highlighted its drawbacks, in disrupting participants’ activities and providing limited insights to the remote researcher. We propose a mixed approach that combines field studies with systematic lab-based Experience Sampling in four steps: a) context exploration - identifying unexpected usage contexts through field studies that rely on passive life logging and ethnographic techniques, b) scenario synthesis –combining the insights into scenarios that will be tested in the lab, c) context reanimation - real life context is reanimated in a CAVE-like virtual environment b) systematic ESM probing - observer-triggered ESM is employed increase the researchers control over the moments of sampling.
Keywords: Experience Sampling Method; Virtual Environments